An Abnormal Pattern of Adenosine Diphosphate-Induced Platelet Aggregation in Acute Myocardial Infarction - Zahavi, J; Dreyfuss, F (Thrombosis and Haemostasis, 1969)
Platelet aggregation as induced by A.D.P. has been studied using the fragiligraph. With this instrument continuous registration for 60 min of the aggregation - disag gregation - behaviour of platelet rich plasma (P.R.P.) has become practicable and a number of parameters of the curves could then be defined and analysed. Specimens from 24 male patients with acute myocardial infarction and 14 normal controls were compared. P.R.P. of the controls exhibited a short phase of an initial rise in optical density (O.D.) lasting 10-20 sec, a phase of decreasing O.D. (5 min), pointing to platelet aggregation and a phase of disaggregation afterwards. The samples of the myocardial patients differed clearly in several aspects : in most of them (18) the initial rise in O.D. was absent and aggregation started immediately; it was though slower but reached a greater extent. The time of maximum aggregation was significantly greater in the patients and there was no overlap with the controls. Coarse aggregates were clearly visible. Final disaggregation was either minimal or absent. At a concen tration of A.D.P. 0.59 γ/ml, the aggregation curve was biphasic in most patients, whereas it was monophasic in the controls. The curves obtained were mathematically analysed including the definition of a parameter called “aggregation time”, τ, and an attempt was made to clarify several of the properties of the curves in terms of platelet behaviour.